Phase-locking of superimposed diffractive gratings in photoresists - Freschi, A. A.; dos Santos, F. J.; Rigon, E. L.; Cescato, L. (Elsevier B.V., 2002)
The superposition of optical interference patterns in a photoresist film can produce a rich variety of diffractive structures. In particular, a periodic non-sinusoidal surface relief profile can be synthesized by adding the Fourier components (sinusoidal gratings) of the desired profile. In order to control the shape of the grooves it is very important an accurate adjustment of the relative spatial shift between the recorded sinusoidal components. We describe the implementation of an opto-electronic feedback loop to select and lock such spatial shift at any desired position, thus allowing the synthesis of structures varying from symmetrical to asymmetrical relief profiles in a continuous range. To demonstrate the feasibility of the technique, the Fourier synthesis of two spatial harmonics is accomplished. The superposed sinusoidal gratings were recorded in positive photoresist films using a holographic setup operating at the line lambda = 457.9 run of an argon-ion laser. A detailed description of the procedure as well as the resulting profiles recorded in the photoresist is presented. (C) 2002 Elsevier B.V. B.V. All rights reserved.